STEREOTYPES AS CHILDREN’S PERCEPTIVE JEALOUSY REPRESENTED IN A.A. MILNE’S POEM IN THE FASHION: A STUDY OF RIFFATERRE’S SEMIOTICS - Rosyidi, Mohamad Ikhwan; Rodiyah, Rodiyah; Farida, Alief Noor (Universitas Negeri Surabaya, 2025)
A study on the representation of stereotypes in A.A. Mille's poem In the Fashion explores Riffaterre's semiotic theory. It exposes explanation of the way stereotype operating in children’s perspective on having jealousy or envy. This poem mostly explores the stereotype of having attractive particular part of body creating opposition, questions, contradiction, and marginalization. This study using qualitative data analysis applied Riffaterre's semiotic theory on poetry (Riffaterre, 1978). The stages of reading, heuristic and hermeneutic readings, would be the steps to do this analysis. The study resulted Milne recently emphasized the tail as part of animal body which has its particular fine quality that the quality of the tail heuristically is exposed and pointed at. The exposure of its quality is done by relating all lines in the poem with the existence and concern of the tail itself. And, Milne exposed, as the hypogram, those as means of learning children about mirroring activities as an effect of stereotyping which is perceived as the representation of what most children have recently seen from the oppositions, contradiction, similarity, and marginalisation.